Pelecehan Seksual pada Remaja dan Implikasinya terhadap Layanan Bimbingan dan Konseling: Studi Kepustakaan - Latiffa Amanda Putri Nur; Dwi Erma Nadhifa; Risma Anita Puriani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Adolescence is a period of development characterized by rapid physical, emotional, and social changes, making adolescents vulnerable to various forms of violence, including sexual harassment. This phenomenon occurs in various contexts, including family, school, community, and digital environments, and has serious impacts on adolescents' psychological, social, and academic well-being. This study aims to comprehensively examine the phenomenon of sexual harassment among adolescents and its implications for guidance and counseling services in educational settings. The method used is a literature review by reviewing various relevant scientific articles from the past six years obtained through electronic databases. The analysis process was carried out using content analysis techniques by grouping findings based on main themes, namely forms of sexual harassment, risk factors, impacts, and the role of guidance and counseling services. The results of the study indicate that sexual harassment among adolescents occurs in various forms, both directly and through digital media, with complex causal factors encompassing individual, family, social, and cultural aspects. The impacts are not only physical, but also psychological and social in the long term. Guidance and counseling services play a crucial role in preventive, curative, and developmental efforts through education, mentoring, and strengthening students' social skills. The implications of this research emphasize the importance of strengthening guidance and counseling services as a systematic strategy in creating a safe and responsive school environment to cases of sexual harassment in adolescents.